Theory and Policy in International Relations - Ullman, Richard H. (Richard Henry); Tanter, Raymond (Book collections on Project MUSE., 1972)
A group of leading political scientists assess the relevance and usefulness of international relations theory for policymaking. The editors' introduction reviews the "state of the art," the importance and liabilities of theory for the policymaker, and the problems of organizing knowledge to meet the needs of the policy community.Originally published in 1972.The Princeton Legacy Library uses the latest print-on-demand technology to again make available previously out-of-print books from the distinguished backlist of Princeton University Press. These editions preserve the original texts of these important books while presenting them in durable paperback and hardcover editions. The goal of the Princeton Legacy Library is to vastly increase access to the rich scholarly heritage found in the thousands of books published by Princeton University Press since its founding in 1905.